Answer:
The equation of parabola is standard form is ![x=\left(y+4\right)^2+2](https://tex.z-dn.net/?f=x%3D%5Cleft%28y%2B4%5Cright%29%5E2%2B2)
Step-by-step explanation:
Given equation of parabola is,
![y^2+8y-x+18=0](https://tex.z-dn.net/?f=y%5E2%2B8y-x%2B18%3D0)
In order to find the equation of parabola in standard form, eliminate x from left side of equation and use completing square method to find the equation.
First step is to add x on both side of equation.
![y^2+8y-x+18+x=0+x](https://tex.z-dn.net/?f=y%5E2%2B8y-x%2B18%2Bx%3D0%2Bx)
![y^2+8y+18=x](https://tex.z-dn.net/?f=y%5E2%2B8y%2B18%3Dx)
Rewriting,
![x=y^2+8y+18](https://tex.z-dn.net/?f=x%3Dy%5E2%2B8y%2B18)
Now applying completing square method as follows.
Following are the steps for calculation of this method.
Find the last term of above equation by using below formula,
![Last\:term\:of\:square=\left(\dfrac{coefficient\:of\:y}{2}\right)^{2}](https://tex.z-dn.net/?f=Last%5C%3Aterm%5C%3Aof%5C%3Asquare%3D%5Cleft%28%5Cdfrac%7Bcoefficient%5C%3Aof%5C%3Ay%7D%7B2%7D%5Cright%29%5E%7B2%7D)
Now coefficient of y is 8.
![\therefore Last\:term\:of\:square=\left(\dfrac{8}{2}\right)^{2}](https://tex.z-dn.net/?f=%5Ctherefore%20Last%5C%3Aterm%5C%3Aof%5C%3Asquare%3D%5Cleft%28%5Cdfrac%7B8%7D%7B2%7D%5Cright%29%5E%7B2%7D)
Simplifying,
![Last\:term\:of\:square=\left(4\right)^{2}](https://tex.z-dn.net/?f=Last%5C%3Aterm%5C%3Aof%5C%3Asquare%3D%5Cleft%284%5Cright%29%5E%7B2%7D)
![Last\:term\:of\:square=16](https://tex.z-dn.net/?f=Last%5C%3Aterm%5C%3Aof%5C%3Asquare%3D16)
Second step is to add and subtract the last term.
![x=y^2+8y+18+16-16](https://tex.z-dn.net/?f=x%3Dy%5E2%2B8y%2B18%2B16-16)
Rewriting,
![x=y^2+8y+16+18-16](https://tex.z-dn.net/?f=x%3Dy%5E2%2B8y%2B16%2B18-16)
Since ![\left(a+b\right)^{2}=a^{2}+2ab+b^{2}](https://tex.z-dn.net/?f=%5Cleft%28a%2Bb%5Cright%29%5E%7B2%7D%3Da%5E%7B2%7D%2B2ab%2Bb%5E%7B2%7D)
Using above formula,
![x=\left(y+4\right)^{2}+2](https://tex.z-dn.net/?f=x%3D%5Cleft%28y%2B4%5Cright%29%5E%7B2%7D%2B2)
Therefore, the equation of parabola in standard form is ![x=\left(y+4\right)^{2}+2](https://tex.z-dn.net/?f=x%3D%5Cleft%28y%2B4%5Cright%29%5E%7B2%7D%2B2)